Rum Across the Border The Prohibition Era in Northern New York - Everest, Allan S. (Syracuse University Press, 1978)
During the boisterous days of American Prohibition, the Lake Chaplain region of New York State teemed with bootleggers, all hoping to make a fast buck smuggling Canadian liquor across the border. In this lively account of that era, Everest's sources-smugglers, local people, and customs officials-recall that if there was a way to smuggle booze, whether by road, rail, or water, it was tried at Rouses Point, New York, the site of a busy U.S. customs station on the Montreal-New York "Rum Trail." The Temperance and Prohibition movements in New York State, controversial federal legislation, its enforcement, the smugglers' ingenuity, their rivalries, the profits, smuggling goods into Canada, the cars, female smugglers, illegal aliens, Canadian breweries, the speakeasies in New York City, the chases, the captures, the courts, and even the weather - all are part of the story. The generation who lived through those raucous days will remember that this is indeed how it was. A map, sixteen illustrations, and regional ballads are included.